Antimicrobial Activity of Kaffir Lime Peel Extract against Streptococcus mutans - Rosalie Purwanto; Jeni Pabontong; Ery Susiany Retnoningtyas; Wenny Irawaty (Dept. of Chemical Engineering, Diponegoro University, 2018)
Kaffir lime peels contain polyphenols as natural antioxidant and antimicrobial agent. The aims of this study were to (1) extract phenolics compounds from kaffir lime peels using water, ethanol 70% and ethanol 96% as the solvent, and (2) assess the antibacterial activity of the extract against Streptococcus mutans which is the main cause of dental caries. Research methodology includes preparation and extraction of polyphenols from kaffir lime peels, preparation of mouthwash based-kaffir lime peels extracts and evaluation the mouthwash ability to inhibit the growth of Streptococcus mutans. The results show water exhibited the best solvent to extract polyphenols among the three solvents. The total phenolics content in the water extract was observed at 11.42±0.48 mg GAE/g, whilst in the two ethanolic extracts were 10.91±0.87 and 8.87±0.53 mg GAE/g for ethanol 70 and 96%, respectively. Consequently, the water-based extract performed the highest antimicrobial activity. The highest inhibition zone was demonstrated by 100% extract of concentration extract variation. Although the inhibition zone of the mouthwash was smaller than the commercial product, the extract has the potential to be developed as a safe mouthwash for long-term usage.Keywords: dental caries; kaffir lime; mouthwash; peel; phenolic; Streptococcus mutans